Sea water corrosion behaviour of T2 and 12832 copper alloy materials in different sea areas. (18th August 2019) - Ding, Kangkang; Fan, Lin; Yu, Mingjie; Guo, Weimin; Hou, Jian; Lin, Cunguo
ABSTRACT: Field exposure test was carried out to investigate the sea water corrosion behaviour and rules of T2 and 12832 copper alloy materials in different sea areas. The corrosion morphology characteristics and corrosion products properties were analysed using different techniques, and the main environmental factors influencing their corrosion rates were discussed by applying grey relational analysis. Reaults showed that with the decrease of the latitude, the corrosion rate of T2 increased, and grey relational analysis indicated that temperature had a significant influence on it. For 12832 copper alloy, the corrosion rate was lower than that of T2 on the whole. Different degree of biofouling occurred on 12832 copper alloy, and the surface fouling conditions (including sediment deposition) had a crucial impact on its corrosion behaviour. In summary, 12832 copper alloy had a better corrosion resistance, but accompanied by de-Mn and de-Al corrosion.